Understanding Digital Network Engagement: Aiding Resistance and Appropriation of Technology - Spencer-Scarr, Diane (AoIR Selected Papers of Internet Research, 2013)
Some individuals actively appropriate and resist the impact of digital network technology while others passively accept. Understanding this complex process of human-technology engagement provides insights to its effect: amplifying or diminishing human behavior. Correlations between personality, decision-making style and engagement have been identified from in-depth interviews and self-reporting surveys, revealing two major groups; ’engaged-but-unaware’ and ’engaged-and-aware’. The distinction was established by utilizing an ecological approach to ’digital networks’ as a tool where the human-tool as a synthesized unit is evaluated within its environment. Engagement was found to involve a suite of behaviors 1) intensity and embededness, 2) responsiveness to feedback, 3) decision-management and 4) motivators. When taken together they form a conceptual model explaining why some individuals resist and appropriate digital network technology to their advantage while others passively accept and are managed by the technology. This paper is part of ongoing research into understanding digital network engagement.